2013
DOI: 10.1063/1.4775786
|View full text |Cite
|
Sign up to set email alerts
|

Strong electron and ion emissions induced by a pyroelectric crystal

Abstract: A novel method of high voltage pulse generation was developed, based on charging a capacitor by changing the temperature of a pyroelectric crystal. A high voltage pulse is formed when a miniature spark gap device in connection with the charging capacitor is suddenly switched on. This high voltage pulse is then used to trigger strong electron and ion emissions from a ferroelectric cathode. The developments of voltage and emission with time were compared with those when the voltage pulse was produced by an exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…3 He detected X-rays emitted from a gold foil target adjacent to a pyroelectric crystal of cesium nitrate (CsNO 3 ) by changing the temperature of the pyroelectric crystal at a pressure of 10 3 Pa. Since his discovery, pyroelectric crystals have contributed to the miniaturization of X-ray generators, 4-9 electron beam generators, [10][11][12][13][14][15] ion generators, 14,16 neutron generators, [17][18][19][20] X-ray fluorescence measurement setups, 21 X-ray absorption fine structure measurement setups, 22 mass spectrometry, 23 and cathodoluminescence spectrometer 24 because a high-voltage power supply is no longer required.…”
Section: Introductionmentioning
confidence: 99%
“…3 He detected X-rays emitted from a gold foil target adjacent to a pyroelectric crystal of cesium nitrate (CsNO 3 ) by changing the temperature of the pyroelectric crystal at a pressure of 10 3 Pa. Since his discovery, pyroelectric crystals have contributed to the miniaturization of X-ray generators, 4-9 electron beam generators, [10][11][12][13][14][15] ion generators, 14,16 neutron generators, [17][18][19][20] X-ray fluorescence measurement setups, 21 X-ray absorption fine structure measurement setups, 22 mass spectrometry, 23 and cathodoluminescence spectrometer 24 because a high-voltage power supply is no longer required.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the cases when the charge collection anode was a plate connected to an external power source discussed earlier, or a Faraday Cup [24,25], the conclusion that the emission increased with increasing extracting voltage was the same. However, there were some differences.…”
Section: Pyroelectric Crystal Induced and Extracted Electron Emissionmentioning
confidence: 60%
“…No external pulse generator was needed. Instead, a high voltage was generated by changing the temperature of a pyroelectric crystal, and in conjunction with a miniature spark gap switching device, a high voltage pulse was generated and then used to trigger strong FEE [24,25]. It has been concluded that when a negative pulse was applied to the front electrode of the cathode, the electron emission current and total charges were the greatest when there was no extracting voltage [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…One such compact source is an electron accelerator and an x-ray generator based on: the pyroelectric effect in vacuum, using single crystals (as a rule, lithium niobate or lithium tantalate) [1 -3] or ceramics [4,5] and the triboelectric effect in vacuum [6,7]. Pyroelectric sources can be used: as an emitter of electrons and ions [8,9] and a neutron generator [10 -13]; in installations for measuring x-ray fluorescence [14]; in mass spectrometry [15]; in an electron probe microanalyzer [16]; and, in a cathode-luminescence spectrometer [17]. Research is being conducted on the operation of a pyroelectric source in a pulsed mode [18,19].…”
mentioning
confidence: 99%